The Impact of Oral Sodium Chloride Supplementation on Thrive and the Intestinal Microbiome in Neonates With Small Bowel Ostomies: A Prospective Cohort Study - Trautmann, Tina; Bang, Corinna; Franke, Andre; Vincent, Deirdre; Reinshagen, Konrad; Boettcher, Michael (Frontiers in Immunology, 2020)
Background: Infants with ileostomies often suffer from sodium depletion, ultimately leading to a failure to thrive. Moreover, early-infantile microbial dysbiosis may potentially aggravate weight faltering. Given that sodium supplementation has been used to restore weight gain and feeding practices largely determine infantile microbiota, the current study investigated the effect of sodium chloride (NaCl) on weight gain and intestinal microbiome in infants with jejuno- and ileostomies. Methods: A prospective cohort study including 24 neonates with enterostomies compared 19 subjects receiving oral NaCl (5.85%) to five subjects without supplementation with respect to postoperative changes in thrive and the intestinal microbiome. Results: Infants receiving NaCl after enterostomy-surgery showed vastly improved weight gain and an increased abundance of Lactobacillus in fecal samples, as compared to subjects without oral supplement who displayed decreasing percentiles for weight and did not reveal a higher abundance of probiotic strains within the ostomy effluent. Contrarily, Klebsiella was equally enriched in supplemented infants, reflecting a higher susceptibility for infections in preterm neonates. Discussion: Our findings support oral NaCl supplementation as a mainstay of postoperative treatment in infants with small bowel ostomies who are predisposed to suffer from a sodium depletion-associated failure to thrive. Not only does NaCl promote weight gain by increasing glucose resorption, but it also appears to induce microbial restoration by enhancing the abundance of health-promoting probiotic bacteria. This finding has an even greater significance when facing an elevated Klebsiella/Bifidobacteria (K/B) ratio, believed to represent an early-life microbial biomarker for development of allergic disease.